Shared hub genes in membranous nephropathy and kidney renal clear cell carcinoma: investigating molecular overlap and tumor progression - Hui, Peng; Shuwen, Zhang (Discover. Oncology, 2025)
Background Membranous nephropathy (MN) and kidney renal clear cell carcinoma (KIRC) are distinct kidney diseases with potential shared molecular mechanisms. Identifying common biomarkers may improve our understanding of disease pathogenesis and provide novel diagnostic and therapeutic targets. Methods The study primarily employed bioinformatics tools to analyze publicly available datasets to identify differentially expressed genes (DEGs) and hub genes in KIRC and MN. Functional interactions of the common DEGs were explored using protein–protein interaction (PPI) networks, and hub genes were further investigated through gene expression databases such as GSCA and UALCAN. Gene Set Enrichment Analysis (GSEA) was used to assess functional enrichment and tumor-driving potential. These bioinformatic results were then experimentally validated by knocking down FYN and LGALS8 in 786-O cells using siRNA, followed by RT-qPCR, protein analysis, and functional assays. Results The study identified four hub genes (FYN, LGALS8, MAGI2, and WT1) in KIRC and MN, with FYN and LGALS8 upregulated and MAGI2 and WT1 downregulated. Bioinformatics validation showed excellent diagnostic performance and confirmed methylation and mutation patterns. Higher FYN and LGALS8 expression were linked to poorer survival. miRNA downregulation was validated in KIRC cell lines. Functional analysis revealed that FYN and LGALS8 promote KIRC progression through the ErbB signaling pathway, and knockdown experiments reduced cell proliferation, migration, and colony formation. Conclusion Our findings identify FYN, LGALS8, MAGI2, and WT1 as hub genes in KIRC, with potential diagnostic and prognostic value. These genes play significant roles in methylation, mutation, and immune regulation in KIRC. However, the results from the limited MN samples suggest possible roles of these genes in MN pathology, but further studies are required to fully assess the relevance of these findings to MN.